BUSINESS & PUBLIC AFFAIRS FORTNIGHTLY VOLUME X, NUMBER 8 - MOORE M; PHILLIPS K (Tufts Archival Research Center, 2007)
Article from "Business and Public Affairs Fortnightly" discussing strength and visibility of tobacco lobby. Focuses on alliances tobacco has made with arts organizations, labor unions, and minorities. Also discusses tax and state legislative alliances. Claims that "tobacco industry isn't going to go down easily."